Perpustakaan Tun Abdul Razak UCS (PTAR) / Amirul Asyraf Ali, PTAR, Hazri Shahrulizwan Hashim and Muhammad Zulkarnain Md Ariff. - Ali, Amirul Asyraf; Hashim, Hazri Shahrulizwan; Md Ariff, Muhammad Zulkarnain (Faculty of Art & Design, Universiti Teknologi MARA Cawangan Puncak Alam, 2019)
Library Tun Abdul Razak (PTAR) Puncak Alam Campus has started its services on 27 July 2009 at 5th Floor. Plaza Satellite Building B (PSB). Through Phase 2 development. Puncak Alam Campus Library has moved into new buildings and fully operation in May 2014. The new building has four floors that can accommodate 1300 seats at a time. The facilities and services provided is expected to meet the needs of teaching, learning, research and development of knowledge among UiTM.